Assemblage. (New York : Kent Fine Art Inc., 1987)
Arman ; Arp, Jean ; Berman, Wallace ; Bourgeois, Louise ; Cornell, Joseph ; Duchamp, Marcel ; Ernst, Max ; Foulkes, Llyn ; Herms, George ; Hesse, Eva ; Jess ; Kienholz, Ed & Nancy ; Kounellis, Jannis ; Man Ray ; Ossorio, Alfonso ; Rauschenberg, Robert ; Schwitters, Kurt ; Tanning, Dorothea ; Wesselmann, Tom ; Westermann, H.C.
Assemblage, KENT Fine Art Inc., New York, May 12 - July 2, 1987
boek